Challenges and Alternative Solutions for Implementing Chemistry Practicums in Public High Schools - Nabila, Suci; Sulastri, Sulastri; Winarni, Sri; Zulfadli, Zulfadli; Khaldun, Ibnu; Mohtar, Lilia Ellany (Jurnal Tadris Kimiya, 2024)
Laboratories play a crucial role in enhancing learning experiences, verifying scientific concepts, and solving problems through scientific methods. However, the implementation of chemistry practicums in schools often faces significant challenges. This study aims to identify the problems hindering the implementation of chemistry practicums and propose alternative solutions to address these issues. A survey method was conducted using a qualitative descriptive approach. The population consisted of 45 schools in Aceh, involving 981 grade XII students. A cluster sampling technique selected 13 schools, comprising 80 participants, including principals, chemistry teachers, and students. Data were collected through validated instruments, including observation sheets, response questionnaires, interviews, and documentation. The findings revealed several obstacles, including inadequate laboratory infrastructure, unprepared teachers, insufficient tools and materials, limited supporting facilities, and a lack of laboratory staff. To overcome these challenges, alternative solutions were suggested, such as conducting practicums in classrooms through demonstrations, utilizing natural materials and virtual media, aligning practicums with learning standards, adopting blended learning models, and recruiting laboratory staff. These proposed solutions provide practical approaches to improving chemistry practicum implementation in public high schools, ensuring students gain hands-on learning experiences and enhancing their understanding of scientific concepts.